Detection of Hepatitis C Infection in Voluntary Blood Donors at PMI Sleman Yogyakarta Using Molecular Methods - Dewi Nur Anggraeni (LPPM Universitas dr. Soebandi, 2024)
Background: Hepatitis C remains one of the major health problems in the world. Nearly 500,000 deaths are reported each year as a consequence of HCV-related complications. One of the risks of transmission of the hepatitis C virus is through blood transfusions. Enzyme Chemiluminescence Immunoassay is one of the standard methods in blood services to detect HCV in donor blood. However, this method still has limitations in detecting HCV when it is in the window phase of the period. Therefore, molecular techniques such as PCR can be performed to detect HCV genetic material. Purpose: To detect Hepatitis C infection in voluntary blood donors at PMI Sleman Yogyakarta using the molecular method Methods: The design of this study is descriptive research with a cross-sectional study design. This research was conducted from September 2022 to February 2023. This research was carried out at PMI Sleman, Yogyakarta. The sample in this study is voluntary donor blood recorded at PMI Sleman in 2022. The sample has undergone the IMLTD test of the ECHLIA method for 45 people with non-reactive results. The sampling technique of this study uses purposive sampling. The data analysis technique in this study uses a descriptive approach. Blood samples were examined using the Real-Time PCR/qPCR method. Results: Sample No.3 showed the presence of an amplification curve and crossed the threshold line at the value of Ct/Cq = 24.29, but this result showed a negative result. It is because the amplification curve that shows positive HCV appears at Ct 29.46, 29.30, 28.48, 28.22, 31.09, 33.78, and 36.87. Conclusions: All blood samples of non-reactive IMLTD donors using the ECHLIA method showed negative results because the genetic material of HCV was not found using the qPCR method.